Dating the Morasko meteorite fall by natural thermoluminescence of the fusion crust - Fedorowicz, Stanisław; Stankowski, Wojciech T.J. (Instytut Geologii UAM, 2016)
The date of fall of the Morasko iron meteorite was determined by means of thermoluminescence measurements of the fusion crust and related local materials. Three small pieces, commonly referred to as ‘shrapnel’, were used. The results obtained are 4.5–5.0 ka, which is in good agreement with previous estimates of 4–6 ka on the basis of radiometric, do- simetric and palynological methods.
Keywords: iron meteorite; terrestrial age; dosimetry; Poland